2005
DOI: 10.1080/153765291009804
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Rat Intestinal Epithelial Cells and Resident Gut Bacteria: (I) Effect of Hexavalent Chromium

Abstract: Toxicants including heavy metals reaching the intestine following ingestion through food and water primarily interact with an ecosystem of eukaryotic and prokaryotic cells. Gut bacteria having a dynamic interrelationship with intestinal epithelial cells are known to play important and specific metabolic, trophic, and protective functions. The present study was undertaken to compare the effects of hexavalent chromium on rat intestinal epithelial cells and the resident gut bacteria following in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Growth and multiplication of bacteria is an important parameter to study the response to toxic insults as it reflects directly to the viability of the bacterial population. The study conducted by Upreti et al (2006) also revealed a concentration dependent inhibition on in vitro exposure of gut flora to arsenic. Here this study showed that in chronic exposure to arsenic, the colony count of E. coli was decreased in arsenic exposed controls and severely decreased in arsenicosis patients in relation to healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Growth and multiplication of bacteria is an important parameter to study the response to toxic insults as it reflects directly to the viability of the bacterial population. The study conducted by Upreti et al (2006) also revealed a concentration dependent inhibition on in vitro exposure of gut flora to arsenic. Here this study showed that in chronic exposure to arsenic, the colony count of E. coli was decreased in arsenic exposed controls and severely decreased in arsenicosis patients in relation to healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Though a few studies have been carried out to see the interactions between gut flora and arsenic (Upreti et al, 2006), still then researchers findings showed that hepatic methylation of inorganic arsenic produce MMA III and DMA III which are considered to be more toxic (Stylbo et al, 2002;Vahter, 2002;Gamble et al, 2005). On the other hand, gut flora produce MMA V and DMA V (Bently and Chasteen, 2002) which are relatively non-toxic and finally TMA III in gaseous form (Qin et al, 2006) whose volatilization lowers arsenic concentration in the body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingested arsenic must undergo detoxification, in order that it is removed from the body, a process brought about by the liver, gut flora also plays a role in arsenic detoxification 8 . Although little work have been carried out to see the interaction between gut flora and arsenic 9 . Recent data suggest that hepatic methylation of arsenic leads to the formation of DMA-III and MMA-III which increases toxicity 10 , so more and more stress is being given on bacterial detoxification of arsenic which is considered to be non-toxic 11 .…”
Section: Introductionmentioning
confidence: 99%